In vitro evaluation of fracture resistance of crown restorations fabricated from different hybrid ceramic materials - Kadhim, Qutada Ismael Kadhim (My University, 2019)
Amaç: Bu çalışmanın amacı, CADCAM sisteminde farklı hibrit seramik malzemelerden üretilen kron restorasyonların kırılma direncini değerlendirmektir. Gereç ve Yöntemler: Çekilmiş 45 molar diş, her biri 15 örnek içeren, rastgele 3 gruba ayrıldı. Çıkarıler dişler, otopolimerize edici akrilik reçine bloklarına yerleştirildi. Tüm dişler standart diş kesim prosedürlerine göre chamfer bitiş çizgisile hazırlandı. CAD/ CAM sistemi (CEREC Omnicam Sistemi, Salzburg, Österreich) ile dijital ölçüler alındi. Taramadan sonra, 45 diş 3 gruba ayrıldı. kron restorasyonları 3 farklı CAD / CAM bloğundan (IPS e.max CAD, Vita Enamic ve GC Cerasmart) üretildi. Restorasyonların simantasyonundan sonra kırılma direnci üniversal test cihazı (Shimadzu product, Kyoto 604-8511, Japan) ile ölçüldü. Veriler toplandıktan sonra sonuçlar istatistiksel olarak değerlendirildi.Bulgular: Sonuçların analizi tüm gruplar arasında istatistiksel olarak anlamlı fark gösterdi (P <0.05). CeraSmart grubu, E-max (2614.47 ± 578.79) ve VitaEnamic gruplarına (1687.90 ± 570.91) kıyasla en yüksek ortalama kırılma yükü ortalamasını (3135.74 ± 860.91) göstermiştir. Sonuçların analizi Cerasmart ve E-max gruplarının istatistiksel olarak benzer kırık yüklerine sahip olduklarını ve Vita grubundan daha yüksek olduğunu gösterdi.Sonuç: CAD CAM sistemiyle üretilen hibrit malzemeler mükemmel kırılma direnci gösterdi.

Aim: Compared to conventional materials, polymer/ ceramic hybrid composites have the potential to tailor the desirable properties that individual component can offer. The aim of this study is to evaluate the fracture resistance of crown restorations fabricated from different hybrid ceramic materials in CADCAM system. Materials and Methods: 45 extracted molar teeth were divided into 3 groups randomly, each group containing 15 specimens. All teeth were placed in autopolymerizing acrylic resin blocks and they were prepared according to standard tooth preparation procedures with a chamfer finish line. Digital impressions were taken with CAD/ CAM system (CEREC Omnicam System, Salzburg, Österreich). After scanning crown restorations were fabricated from 3 different CAD/ CAM blocks (IPS e.max CAD, Vita Enamic, and GC Cerasmart). After cementation of the restorations, fracture resistance was measured with a universal testing machine (Shimadzu product, Kyoto 604-8511, Japan). After collecting the data, the results were evaluated statistically.Results: Analysis of the results showed statistically significant difference between all the groups (P<0.05). CeraSmart group exhibited the highest mean fracture load mean (3135.74±860.91) compared to E-max (2614.47±578.79) and VitaEnamic groups (1687.90±570.91). Analysis of the results showed that Cerasmart and E-max groups had statistically similar fracture loads and higher than Vita group.Conclusion: Hybrid materials fabricated with CADCAM system showed excellent fracture resistance.
Keywords: CADCAM; Diş; Fracture resistance; Health; Hibrit seramikler; Hybrid ceramics; kırılma direnci CADCAM; Sağlık; Tooth